Cortical bone distribution in the femoral neck of Paranthropus robustus - (:unkn) unknown (My University, 2019)
Studies of the australopith (Australopithecus and Paranthropus) proximal femur have increasingly integrated information from the local arrangement of the cortical and cancellous bone to allow functional-biomechanical inferences on the locomotor behavioral patterns. In Australopithecus africanus and Paranthropus robustus, the cancellous bone organization at the center of the femoral head shows principal strut orientation similar to that of fossil and recent humans, which indicates that australopiths were human-like in many aspects of their bipedalism. However, by combining outer morphology with superoinferior asymmetry in cortical bone thickness at the base of neck and mid-neck, it has been suggested that, while adapted for terrestrial bipedality, australopiths displayed a slightly altered gait kinematics compared to Homo. We used techniques of 2D and 3D virtual imaging applied to an X-ray microtomographic record to assess cortical bone distribution along the entire femoral neck compartment in four upper femora from Swartkrans, South Africa (SK 82, SK 97, SK 3121, and SWT1/LB-2) and compared the results to the extant human and chimpanzee conditions. Our results support and extend previous evidence for more symmetric superior and inferior femoral neck cortical thicknesses in P. robustus than in modern humans and show that the differences are even greater than previously reported. However, P. robustus and humans still share a trend of lateral-to-medial decrease in asymmetry of the superior/inferior cortical thickness ratio, while this pattern is reversed in chimpanzees. We also identified two features uniquely characterizing P. robustus: an accentuated contrast between the relatively thicker anterior and the thinner posterior walls, and a more marked lateral-to-medial thinning of both cortices compared to extant humans and chimpanzees, which indicate wider interspecific differences among hominids in structural organization of the proximal femur than previ
Keywords: African Research